2011
DOI: 10.1007/s10353-011-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

Swedish adjustable gastric banding – an underestimated risk factor for the development of esophageal cancer?

Abstract: Background: Patients with obesity are at higher risk for gastroesophageal reflux disease and also for adenocarcinoma of the distal esophagus.Methods: Case report. Results: We report on a 58-year-old male patient who developed adenocarcinoma of the distal esophagus (Barrett's cancer) 13 years after implantation of a SAGB (Swedish adjustable gastric banding). Predisposition to reflux combined with bad compliance (frequent overeating) lead to dilation of the pouch followed by impairment of the lower esophageal sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Recent studies have attempted to focus on the development of esophageal cancer after bariatric surgery. Most of them are case reports or retrospective single-center analyses [1,4,6,9,22]. Our study includes 10.300 patients following LAGB out of the overall population of Austria (8.5 million).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have attempted to focus on the development of esophageal cancer after bariatric surgery. Most of them are case reports or retrospective single-center analyses [1,4,6,9,22]. Our study includes 10.300 patients following LAGB out of the overall population of Austria (8.5 million).…”
Section: Discussionmentioning
confidence: 99%
“…So far, fewer than 15 cases of esophageal cancer after LAGB implantation have been described, but there is sound evidence that the development of Barrett's metaplasia following LAGB is much higher [1,2,4,9]. The development of esophageal cancer might be based on frequent overeating and a poorly managed gastric band with suboptimal follow-up leading to dilatation of the proximal gastric pouch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, longterm follow-up studies (> 7 years) have shown band dysfunction (insufficient weight loss) and a high rate of band-related complications (esophagitis, band erosion, leakage, and band slippage) in around 50% of patients. Between 32 and 53% of the patients require surgical removal of the band within the first 7 years [1][2][3][4].…”
Section: Introduction/purposementioning
confidence: 99%